2007
DOI: 10.1002/eji.200636542
|View full text |Cite
|
Sign up to set email alerts
|

Arginase activity mediates reversible T cell hyporesponsiveness in human pregnancy

Abstract: Complex regulation of T cell functions during pregnancy is required to ensure materno-fetal tolerance. Here we reveal a novel pathway for the temporary suppression of maternal T cell responses in uncomplicated human pregnancies. Our results show that arginase activity is significantly increased in the peripheral blood of pregnant women and remarkably high arginase activities are expressed in term placentae. High enzymatic activity results in high turnover of its substrate l-arginine and concomitant reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 146 publications
(179 citation statements)
references
References 52 publications
5
168
1
4
Order By: Relevance
“…Similar to observations resulting from Trp metabolism, Arg catabolism was proposed as a mechanism involved in fetal tolerance, after ARG1 activity was shown to be increased in normal term pregnancy (29). Increased Arg catabolism induced T cell hyporesponsiveness through a mechanism involving reduced half-life of mRNA encoding the TCR CD3j chain (30).…”
Section: Discussionmentioning
confidence: 72%
“…Similar to observations resulting from Trp metabolism, Arg catabolism was proposed as a mechanism involved in fetal tolerance, after ARG1 activity was shown to be increased in normal term pregnancy (29). Increased Arg catabolism induced T cell hyporesponsiveness through a mechanism involving reduced half-life of mRNA encoding the TCR CD3j chain (30).…”
Section: Discussionmentioning
confidence: 72%
“…Arginase level has been reported to be significantly increased in the peripheral blood of pregnant women and placenta, leading to the temporary suppression of the maternal immune response during human pregnancy. 8 High levels of arginase activity have been suggested to contribute to T cell dysfunction in human immunodeficiency virus-seropositive patients. 9 High arginase activity, a hallmark of nonhealing leishmaniasis, is primarily expressed locally at the site of pathology and causes local depletion of L-Arg, resulting in impaired T cell responses.…”
Section: Resultsmentioning
confidence: 99%
“…The symbiosis between mother and fetus during pregnancy is not due to immunological ignorance, but a complex transient modulation of the maternal immune response where the adaptive immunity is down-modulated and the innate immune response is enhanced (Muller et al, 2009). It has been reported that there is a temporary suppression of maternal T cell responses by arginase secreted by polymorphonuclear leukocytes in normal pregnancies (Kropf et al, 2007). Thus, there is interplay between the different types of leukocytes to protect the fetus from the maternal immune system.…”
Section: Pregnancymentioning
confidence: 99%